Arabidopsis DNA glycosylase MBD4L improves recovery of aged seeds - Lescano Lopez, Carlos Ignacio; Torres, José Roberto; Cecchini, Nicolás Miguel; Alvarez, María Elena (Wiley, 2024)
DNA glycosylases initiate the base excision repair (BER) pathway by catalyzing the removal of damaged or mismatched bases from DNA. The Arabidopsis DNA glycosylase methyl-CpG-binding domain protein 4 like (MBD4L) is a nuclear enzyme triggering BER in response to the genotoxic agents 5-fluorouracil and 5-bromouracil. To date, the involvement of MBD4L in plant physiological processes has not been analyzed. To address this, we studied the enzyme functions in seeds. We found that imbibition induced the MBD4L gene expression by generating two alternative transcripts, MBD4L.3 and MBD4L.4. Gene activation was stronger in aged than in non-aged seeds. Seeds from mbd4l-1 mutants displayed germination failures when maintained under control or ageing conditions, while 35S:MBD4L.3/mbd4l-1 and 35S:MBD4L.4/mbd4l-1 seeds reversed these phenotypes. Seed nuclear DNA repair, assessed by comet assays, was exacerbated in an MBD4L-dependent manner at 24 h post-imbibition. Under this condition, the BER genes ARP, APE1L, and LIG1 showed higher expression in 35S:MBD4L.3/mbd4l-1 and 35S:MBD4L.4/mbd4l-1 than in mbd4l-1 seeds, suggesting that these components could coordinate with MBD4L to repair damaged DNA bases in seeds. Interestingly, the ATM, ATR, BRCA1, RAD51, and WEE1 genes associated with the DNA damage response (DDR) pathway were activated in mbd4l-1, but not in 35S:MBD4L.3/mbd4l-1 or 35S:MBD4L.4/mbd4l-1 seeds. These results indicate that MBD4L is a key enzyme of a BER cascade that operates during seed imbibition, whose deficiency would cause genomic damage detected by DDR, generating a delay or reduction in germination.